Age: A Demographic Factor Matters To E-Learning in Nepal - Bhusal, Durga (Butwal Campus Journal, 2020)
COVID-19 worldwide pandemic has created the new environment of ability transformation of teachers from organizing traditional classroom learning to manage behavior of their students in electronic learning demanding skill of new technology. It is challenging to achieve positive educational outcomes in Nepal through sound behavior management establishing the environmental context that makes the good instruction and highly effective learning possible. Highly effective instruction reduces, but does not eliminate, students’ behavior problems in both traditional class room and e-learning management. The purpose of this paper is to provide information related to effectiveness of e-learning to improve positive outcomes of teaching regarding educational demographics. Various intellectual properties are reviewed to fulfill the purpose of this paper. Teachers able to break resistance of new technology would be only effective to implement strategies of e-learning and then can appropriately manage the behavior of targeted group of students is crux of this study.